A Methods Engineering Study on Lufthansa Technik Philippines - Rivero, Jessa Ria May D. (College of Engineering, 2005)
Lufthansa Technik Philippines (LTP) was found in the year 2000 as a joint venture of Germany's renowned Lufthansa Technik Aviation Group and Philippine aviation service provider Macro Asia. LTP is an exclusive provider of aircraft-related technical services to Philippine Airlines (PAL). It extends line and base maintenance services to 17 more international customers. It is the Lufthansa Technik Group's prime center for A330/A340 heavy maintenance. The group conducted a systems and procedures study in the company. The study is concerned with the generation and flow of maintenance logs prior to aircraft non-routine maintenance works and systems encoding. The study aims to increase the efficiency of the present system. The present system has been documented by the group and was analyzed using streamline analysis. In the course of the study, it has been observed that the inefficiency in the system results to two things, delay and the absence of accountability. After a thorough analysis of the group came up with several recommendations that involve the cooperation of the Documentation Office, Mechanics, Data Researchers and Planners. The main feature of the proposed system is the implementation of control systems in the GML process so that proper monitoring and accountability among departments involved are covered. The effects of these recommendations will minimize delays and decrease the system's downtimes, therefore, increasing LTP's productivity and improving its efficiency.